Comparison of the conventional CMAC and the D-blade CMAC with the direct laryngoscopes in simulated cervical spine injury-a manikin study - Jain,Divya (2014)
BACKGROUND: CMAC videolaryngoscope has recently been introduced for videoscope guided intubation. The aim of our study was to compare and evaluate the efficacy of the conventional blade and the angulated D blade of the CMAC videolaryngoscope with the direct laryngoscopes in simulated cervical spine injury patients on the airway manikin. MATERIALS AND METHODS: Following power analysis, 33 resident doctors were enrolled to perform endotracheal intubation using all the 4 different laryngoscopes namely the Macintosh laryngoscope, McCoy laryngoscope, conventional CMAC videolaryngoscope and the D blade of the CMAC videolaryngoscopes on the airway manikin in simulated cervical spine injury. The demographic variables of the resident doctors were recorded. The outcomes measured included vocal cord visualization (Cormack-Lehane grading), time taken to intubate, number of attempts for successful intubation and optimizing maneuvers required. RESULTS: The use of indirect videolaryngoscopes resulted in better glottic visualization in comparison to the direct laryngoscopes (CL-I) in 20/33 (60.6%) in the Macintosh group, 24/33 (72.7%) in McCoy group, 30/33 in (90.9%) in Vlc group and 32/33 (96.9%) in Vld group. The time taken to intubate averaged to 15.54 ± 2.6 in Macintosh group, 18.90 ± 4.47 in McCoy group, 20.21 ± 7.9 in Vlc group and 27.42 ± 9.09 in Vld group. The 1st attempt intubation success rate was 84.8% (Macintosh), 72.7% (McCoy), 90.9% (Vlc) and, 78.7% (Vld). CONCLUSIONS: The overall performance of the conventional CMAC blade proved to be the best when compared with the D-blade CMAC, Macintosh blade and the McCoy blade for intubation in simulated cervical spine patients by anesthesia residents.